Peningkatan Dinamika Pembelajaran Matematika melalui Integrasi Model TGT dan Media Interaktif Berbasis TPACK di Madrasah Ibtidaiyah: Improving Mathematics Learning Dynamics through the Integration of the TGT Model and TPACK-Based Interactive Media in Madrasah Ibtidaiyah - Habil, Muhammad Noor; Nastiti, Luvia Ranggi; Sulistyowati, Sulistyowati (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Mathematics learning in elementary schools often faces challenges related to the low level of learning dynamics, characterized by limited student participation, motivation, and engagement during the learning process. Moreover, there is still a lack of comprehensive studies integrating the Team Games Tournament (TGT) model with interactive media grounded in TPACK (Technological Pedagogical and Content Knowledge) to create a more engaging and meaningful learning environment. This study aims to analyze improvements in learning dynamics in mathematics through the implementation of the TGT model, assisted by TPACK–based interactive media, in Islamic elementary schools (Madrasah Ibtidaiyah). The research employed a quantitative approach with a pre-experimental one-group pretest-posttest Design, involving 24 fifth-grade students at MIS Al-Jihad. The research instruments included learning achievement tests, student activity observation sheets, and supporting documentation. The results showed a significant improvement in students’ learning outcomes, with posttest scores higher than pretest scores. The N-Gain test analysis indicated moderate improvement. At the same time, the Wilcoxon Signed Rank Test yielded W = 0 and Wtable = 81 with a p-value of 0.000 < 0.05, indicating a significant difference between students’ learning outcomes before and after the treatment. Therefore, the integration of the TGT model and TP-ACK–based interactive media is proven to be effective in enhancing the dynamics of mathematics learning, both in terms of student activity and learning achievement at the elementary school level.